A Novel Rice Curl Dwarf-Associated Picornavirus Encodes a 3C Serine Protease Recognizing Uncommon EPT/S Cleavage Sites - Zhang, Tianze; Li, Chenyang; Cao, Mengji; Wang, Dan; Wang, Qi; Xie, Yi; Gao, Shibo; Fu, Shuai; Zhou, Xueping; Wu, Jianxiang (Frontiers in Microbiology, 2021)
Picornaviruses cause diseases in a wide range of vertebrates, invertebrates and plants. Here, a novel picornavirus was identified by RNA-seq technology from rice plants showing dwarfing and curling symptoms, and the tentative name rice curl dwarf-associated virus (RCDaV) is proposed. The RCDaV genome consists of an 8987 nt positive-stranded RNA, excluding a poly(A) tail, encoding two large polyproteins. Using in vitro cleavage assays, we have identified that the RCDaV 3Cprotease (3Cpro) as a serine protease recognizes the conserved EPT/S cleavage site which differs from the classic Q(E)/G(S) sites cleaved by most picornaviral 3C chymotrypsin-like cysteine proteases. Therefore, we comprehensively deciphered the RCDaV genome organization and showed that the two polyproteins of RCDaV can be cleaved into 12 mature proteins. We found that seven unclassified picornaviruses also encode a 3Cpro similar to RCDaV, and use the highly conserved EPT/S as the cleavage site. The precise genome organizations of these viruses were illustrated. Moreover, RCDaV and the seven unclassified picornaviruses share high sequence identities and similar genome organizations, and cluster into a distinct clade in the order Picornavirales. Our study provides valuable information for the understanding of picornaviral 3Cpros, deciphers the genome organization of a few relatively obscure picornaviruses, and lays the foundation for further pathogenesis research on these viruses.